2012
DOI: 10.1088/1742-6596/343/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Dressing approach to the nonvanishing boundary value problem for the AKNS hierarchy

Abstract: Abstract. We propose an approach to the nonvanishing boundary value problem for integrable hierarchies based on the dressing method. Then we apply the method to the AKNS hierarchy. The solutions are found by introducing appropriate vertex operators that takes into account the boundary conditions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…The DNLSE-I (26) arises from the second positive flow, while the Mikhailov model (35) is obtained from the first negative flow. The gauge transformation (38) connects the system (24) to (39), which in particular yields relations between the three kinds of DNLS equations, namely, (26), (40) and (41). Furthermore, we have demonstrated a general relation between the model (35) and the massive Thirring model (45) through (48).…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The DNLSE-I (26) arises from the second positive flow, while the Mikhailov model (35) is obtained from the first negative flow. The gauge transformation (38) connects the system (24) to (39), which in particular yields relations between the three kinds of DNLS equations, namely, (26), (40) and (41). Furthermore, we have demonstrated a general relation between the model (35) and the massive Thirring model (45) through (48).…”
Section: Discussionmentioning
confidence: 75%
“…where A = 8c (2c − 1), B = 4c and C = 4 (1 − c). Note that in (39) we have a fifth-order nonlinearity and two types of derivative nonlinear terms. Let us use the same transformation leading to equation ( 26), i.e.…”
Section: Relations Between Dnls Type Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fields in B are directly related to the famous tau functions, obtained by projecting (6.2) between the highest weight states of the algebra (for more details we refer the reader to [24,25]). The adjoint relations are E j…”
Section: Akns Solutionsmentioning
confidence: 99%
“…It has been shown that the AKNS equations are completely integrable. The researches about AKNS equations are in progress up to now [9][10][11]. In this paper, we will present a nonlinear evolution equation on the basis of the AKNS equations.…”
Section: Introductionmentioning
confidence: 99%